Study Space at Home and the Role of Interior Architecture Design in a Post-Pandemic - Ali, Osama Hassan Ismail; Ismail, Mahmoud Ahmed (Dirasat: Human and Social Sciences, 2026)
Objectives: This study explored the interior design of home study areas and the impact of the pandemic on the necessity of remote learning. It highlighted principles and standards specific to designing such spaces, which are often absent or inadequately equipped in modern homes. The study aimed to demonstrate the importance of designing these spaces with pandemic implications in mind, presenting a design model to meet residents' needs. It examined the role of interior design in creating these spaces, reducing disease spread, and helping residents adapt to the pandemic’s conditions. The hypothesis discussed was that appropriate study space designs can fulfill residents' needs, particularly during quarantine periods, allowing them to effectively study and maintain health and safety. Methods: The study used descriptive, analytical, and quantitative methodologies, including a questionnaire, along with an applied approach. Results: The study found that designing spaces suitable for pandemic conditions can meet residents' needs during quarantine and curfew. These designs allow them to study and engage in activities at home while ensuring health and safety. ConclusionS: A proposed design model was presented, illustrating the concept of interior design for home study spaces during epidemic outbreaks.